2020
DOI: 10.1590/1413-7054202044003920
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field in coffee seed germination

Abstract: The effective production of coffee seedlings faces many challenges, including seed germination. Therefore, a reduced seed germination period can be one of the most relevant contributions to enhance the testing and production of robust seedlings. The objective of this research was to evaluate the effects of a constant magnetic field on the germination of coffee seeds (Coffea arabica L.). The analyses were performed using a biospeckle laser (BSL) in conjunction with traditional seed viability tests. The coffee s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, there are also reports on some cases when application of MF on seeds was not successful or repeatable. For some crops, only in certain range(s) of the MF intensity and exposure time have caused the positive effects (Araújo et al, 2016;Farooq et al, 2019;Rifina et al, 2019;Sarraf et al, 2020;), while the other ranges have given weakened or even negative effects (Abdani Nasiri et al, 2018;Nair et al, 2018;Florez et al, 2019;Khaledi et al, 2019;Massah et al, 2019;Migahid et al, 2019;Júnior et al, 2020;Afzal et al, 2021). Due to the complexity of the interaction between the used MF and plants, the research of the mechanism is still in the exploration stage and needs further study (Radhakrishnan, 2019).…”
Section: Modern Scientific and Technological Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also reports on some cases when application of MF on seeds was not successful or repeatable. For some crops, only in certain range(s) of the MF intensity and exposure time have caused the positive effects (Araújo et al, 2016;Farooq et al, 2019;Rifina et al, 2019;Sarraf et al, 2020;), while the other ranges have given weakened or even negative effects (Abdani Nasiri et al, 2018;Nair et al, 2018;Florez et al, 2019;Khaledi et al, 2019;Massah et al, 2019;Migahid et al, 2019;Júnior et al, 2020;Afzal et al, 2021). Due to the complexity of the interaction between the used MF and plants, the research of the mechanism is still in the exploration stage and needs further study (Radhakrishnan, 2019).…”
Section: Modern Scientific and Technological Research Resultsmentioning
confidence: 99%
“…The study on plants' enzyme activities changed by MF treatment were mainly focused on peroxidase (POD) (Bao and Yun, 2010;Anand et al, 2019;Abdel Latef et al, 2020), catalase (CAT) (Anand et al, 2019;Abdel Latef et al, 2020;Harb et al, 2021) and superoxide dismutase (SOD) (Anand et al, 2019;Kataria et al, 2019;Abdel Latef et al, 2020;Harb et al, 2021). Part of the study was also directed to polyphenol oxidase (PPO) (Abdel Latef et al, 2020), nitrate reductase (NR) (Radhakrishnan, 2019;Kataria et al, 2022, malate dehydrogenase (MDH) (Júnior et al, 2020), ascorbic acid peroxidase (APX) (Nyakane et al, 2019;Abdel Latef et al, 2020;Harb et al, 2021), glutathione reductase (GR) (Araújo et al, 2016) and other enzymes, and have shown positive feedback.…”
Section: Enhancement Of Enzyme Activitymentioning
confidence: 99%
“…It has been reported that exposure to MF during seeding results in increased changes in water and mineral metabolism [37]. Exposure to MF seeds also increases enzyme activity in embryos [38], thereby affecting plant growth and physiology and even the final stages of seed processing, such as harvesting mature plants [39]. Shine et al [40] stated that the increase in germination of soybean seeds treated with MF was possible due to reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%